Does the mainland China–Hong Kong exchange program change the views of local university students in Hong Kong on regional cooperation? A randomized control-group pre-test post-test experiment - Liu, Jianzheng; Li, Jie; Zhang, Xiwen; Song, Jing; Li, Weifeng; Wu, Jiansheng (Frontiers in Psychology, 2023)
The Chinese central government has been running an intensive exchange program called Mainland China–Hong Kong Ten Thousand Student Exchange Program since 2012 to support local Hong Kong university students’ visits to mainland China to promote exchange and regional cooperation between Hong Kong and mainland China. However, little is known about local Hong Kong university students’ views on regional cooperation and whether the program is effective in changing their views. Using a randomized experimental design, we found that most students hold positive views on regional cooperation between Hong Kong and mainland China, but a considerable percentage of students oppose integration with mainland China. We also found that the program is effective in changing students’ views on certain aspects of regional cooperation related to the free trade zones and the Hong Kong–Zhuhai–Macau Bridge positively, but not significantly effective on other aspects of regional cooperation. This study provides the first causal quantitative evidence regarding the impact of the mainland China–Hong Kong exchange program on local university students’ views regarding regional cooperation. The findings help inform the public about the prospect of regional cooperation and offer policy implications on youth exchange between mainland China and Hong Kong.